Hydrogen Peroxide Induces α-Tubulin Detyrosination and Acetylation and Impacts Breast Cancer Metastatic Phenotypes - Megan B. Stemberger; Julia A. Ju; Keyata N. Thompson; Trevor J. Mathias; Alexandra E. Jerrett; Katarina T. Chang; Eleanor C. Ory; David A. Annis; Makenzy L. Mull; Darin E. Gilchrist; Michele I. Vitolo; Stuart S. Martin (Cells, 2023)
Levels of hydrogen peroxide are highly elevated in the breast tumor microenvironment compared to normal tissue. Production of hydrogen peroxide is implicated in the mechanism of action of many anticancer therapies. Several lines of evidence suggest hydrogen peroxide mediates breast carcinogenesis and metastasis, though the molecular mechanism remains poorly understood. This study elucidates the effects of exposure to elevated hydrogen peroxide on non-tumorigenic MCF10A mammary epithelial cells, tumorigenic MCF7 cells, and metastatic MDA-MB-231 breast cancer cells. Hydrogen peroxide treatment resulted in a dose- and time-dependent induction of two α-tubulin post-translational modifications—de-tyrosination and acetylation—both of which are markers of poor patient prognosis in breast cancer. Hydrogen peroxide induced the formation of tubulin-based microtentacles in MCF10A and MDA-MB-231 cells, which were enriched in detyrosinated and acetylated α-tubulin. However, the hydrogen peroxide-induced microtentacles did not functionally promote metastatic phenotypes of cellular reattachment and homotypic cell clustering. These data establish for the first time that microtentacle formation can be separated from the functions to promote reattachment and clustering, which indicates that there are functional steps that remain to be identified. Moreover, signals in the primary tumor microenvironment may modulate α-tubulin post-translational modifications and induce microtentacles; however, the functional consequences appear to be context-dependent.